ChemInform Abstract: Efficient Pd‐Catalyzed Direct Arylations of Heterocycles with Unreactive and Hindered Aryl Chlorides. Issue 11 (8th March 2013) - Ghosh, Debalina; Lee, Hon Man
Abstract A wide range of heteroaromatic biaryls, required in organic and drug synthesis, can be prepared and the coupling proceeds with high regioselectivity.